Does breaking gender stereotypes contribute to victimization at school? - Agnich, Laura E. (Criminal justice studies, 2017)
Victimization is a serious problem facing youth in American public schools. Prior research demonstrates that victimization is stratified by sex/gender; however, few studies consider factors that may moderate this relationship. This research investigates if victimization occurs when students break sex/gender stereotypes at school among female and male youth. The broad research question for this study is - are breaking sex/gender stereotypes regarding academic activities, math, and sports associated with victimization for female and male students at school? To address this research question, this study employs nationally representative data from the Education Longitudinal Study (ELS) of 2002 to investigate if breaking sex/gender stereotypes contributes to the likelihood of victimization for female and male students at school. The study finds that females who have favorable attitudes toward math and participate in math-related activities are less likely to be victimized, while students of both sexes who participate in female dominated sports (i.e. cheerleading and softball) have a higher risk of victimization, as do females who participate in male dominated sports (i.e. football and baseball). The implications for future research and policy implementation are discussed.